Joseph Lemuel Saywell correspondence - Saywell, Joseph Lemuel
ALS written by Saywell regarding publication of histories of Anglican parishes in Yorkshire, England.
Anglican clergyman.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Church of England -- History; Yorkshire (England) -- Church history; Clergy